Single-pulse and multipulse longitudinal phase space and temperature measurements of an intense ion beam - J. E. Coleman; P. A. Seidl; F. M. Bieniosek; M. A. Leitner; S. M. Lidia; J. L. Vay; W. L. Waldron; D. P. Grote; D. R. Welch (Physical Review Special Topics. Accelerators and Beams, 2012)
Longitudinal phase space and temperature measurements were conducted on a 2–3  μs long, singly charged K^{+} ion bunch with an ion energy of ∼0.3  MeV and current of 30 mA. The principal objective of these experiments was to measure the longitudinal beam dynamics and study the limits of axial compression. The differences between the measured beam energy, longitudinal beam dynamics, and the amplitude and time history of the Marx voltage waveform were all quantified. Longitudinal phase space measurements indicate a slight chromaticity (<1%) in the beam from head to tail. Record low longitudinal temperatures of T_{z}=2–4×10^{-2}  eV were measured for a beam bunch of this intensity with negligible effects from neutralizing the beam space charge with a background plasma. A qualitative comparison of experimental and calculated results are presented, which include time resolved longitudinal distributions, and phase space of the beam at 430 cm.